Answer :

**Given:**

**To find:** the value of the given expression

**Explanation:** given

As we know,

Substituting this in the given expression, we get

On combining we get,

But we know sin^{2}θ + cos^{2}θ = 1

⇒ sin^{2}θ = 1 – cos^{2}θ

Now substituting the above value in equation (i), we get

= – 1

Hence the given value of the expression is–1

**OR**

**Given:** sin θ = cos θ

**To find:** the value of 2 tan θ + cos^{2}θ

**Explanation:** given sin θ = cos θ

But we know this equal to tan θ.

Hence tan θ = 1

But this is possible for the value

θ = 45°………. (i)

We will take the next expression 2 tan θ + cos^{2}θ.

Substituting the value of θ from equation (i), we get

2 tan (45°) + cos^{2}(45°) ………. (ii)

We know tan (45°) = 1 and cos (45°)

Substituting these values in equation (ii), we get

Hence the value of 2 tan θ + cos^{2}θ = .

Rate this question :